School Counsellors’ Perceptions on Working with Student High-Risk Behaviour - Harris, Gregory E.; Jeffery, Gary (Canadian Journal of Counselling and Psychotherapy, 2010)
The current exploratory-descriptive study used a survey design method to examine guid-ance counsellors’ and educational psychologists’ perceptions of their preparation, motiva-tion, and effectiveness in preventing, assessing, and intervening into student high-risk behaviour. The study also explored training associated with addressing high-risk behaviour along with the perceived responsibility and roles of school counsellors when faced with such behaviour. Views related to the following seven categories of high-risk behaviour were explored: (a) suicide attempts; (b) self-mutilation (e.g., cutting); (c) bullying; (d) extreme school violence (e.g., school shootings, bombings); (e) eating disorders and related behaviour (e.g., extreme exercising); (f) sexual behaviour leading to risk of HIV or other sexually transmitted infections (STIs); and (g) drug-using behaviour (e.g., IV drug use, needle sharing) leading to risk of HIV or other STIs. Implications for training, practice, and research are discussed.